Managing learning (London ; New York : Routledge in association with the Open University, 1994)
This book is divided into five parts: Organizational learning; Assessing and developing competency; Facilitating development; Deveoping team effectiveness; and Managing diversity.
Keywords: Management; Training; Executives; Experiential learning; Executives -- Training of; Management -- Study and teaching; Assessment centers (Personnel management procedure)